ANALYSIS OF THE INTERMEDIATE PRINCIPAL STRESS EFFECT ON MULTISTAGE TRUE TRIAXIAL TEST - Rachmad Iswanto, Dadang
In actual conditions in the field, rock masses will receive different stresses from all directions or can be called nonhydrostatic. Nonhydrostatic can be caused by the presence of cleavage, foliation, schistophytes, micro fissures, macro fissures, stiffness, and bedding. This encourages the development of an independent compression test on each of the stresses called True Triaxial Testing (TTT). True triaxial testing is done by giving variations of intermediate principal stress (?2) of 0.5, 1, 1.5, 2, and 2.5 MPa and minor principal stress (?3) of 0.5, 1, and 1.5 MPa. From this test, the sample compressive strength will be obtained. The results show that with ?3 made fixed and ?2 is increased, resulting in an increase in the maximum major principal stress (?1) that can be borne by the sample. Then the value of ?2 cannot always be considered to be equal to ?3 because it has an effect that cannot be ignored. The exact rock collapse criteria to be used in this test are the Mogi-Coulomb criteria.